Activated CD8+ T cells and natural killer T cells in bronchoalveolar lavage fluid in hypersensitivity pneumonitis and sarcoidosis - Tøndell, Anders; Rø, Anne Dorthea; Børset, Magne; Torolf, Moen; Sue-Chu, Malcolm (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Sarcoidosis and hypersensitivity pneumonitis are diffuse parenchymal lung diseases characterized by formation of non-caseating granulomas with a bronchocentric distribution. Analysis of the white blood cell differential profile in bronchoalveolar lavage fluid can be a useful supplement in the diagnostic work-up. Objective: Diagnostic markers that can improve the discrimination of sarcoidosis and hypersensitivity pneumonitis are wanted. Methods: Bronchoalveolar lavage fluid fractions of CD4+ and CD8+ T cells expressing the activation marker HLA-DR and fractions of natural killer T cells determined by flow cytometry were investigated in sarcoidosis (N=83), hypersensitivity pneumonitis (N=10)  and healthy control subjects (N=15). Results: In hypersensitivity pneumonitis, natural killer T cell fractions were over 7-fold greater [median (IQR): 5.5% (3.5-8.1) versus 0.7% (0.5-1.2), p